2017
DOI: 10.3390/min7070111
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Common Monovalent and Divalent Chlorides on Chalcopyrite Flotation

Abstract: Much attention has been paid to the flotation of chalcopyrite using saline seawater. However, the influence of salt ions on mineral flotation is complex, and different salts may play various roles-either beneficial or detrimental. This study investigated the effects of common chlorides (Cl − ) of Na + , K + , Mg 2+ , and Ca 2+ in seawater on chalcopyrite floatability. The presence of Na + , K + , and Ca 2+ resulted in greater chalcopyrite recovery, with this effect being more pronounced for the monovalent cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
(49 reference statements)
3
26
0
Order By: Relevance
“…A similar deteriorative chalcopyrite recovery in ultrapure water controlled at strong alkaline condition was found by Liu and Zhang [39] while detrimental effects of both salts on chalcopyrite recovery were reported in [17,28]. Nagaraj and Farinato [23] reported that Ca 2+ had a negligible effect while Li et al [16] reported a slightly beneficial effect on chalcopyrite flotation in the solution containing Ca 2+ . The differing flotation behaviors of chalcopyrite in salt solution may be attributed to various collectors (e.g., sodium diisobutyl dithiophosphate vs. sodium butyl xanthate) and pulp densities (35 wt % vs. 8 wt %) [40].…”
Section: Xps Measurementsmentioning
confidence: 50%
See 4 more Smart Citations
“…A similar deteriorative chalcopyrite recovery in ultrapure water controlled at strong alkaline condition was found by Liu and Zhang [39] while detrimental effects of both salts on chalcopyrite recovery were reported in [17,28]. Nagaraj and Farinato [23] reported that Ca 2+ had a negligible effect while Li et al [16] reported a slightly beneficial effect on chalcopyrite flotation in the solution containing Ca 2+ . The differing flotation behaviors of chalcopyrite in salt solution may be attributed to various collectors (e.g., sodium diisobutyl dithiophosphate vs. sodium butyl xanthate) and pulp densities (35 wt % vs. 8 wt %) [40].…”
Section: Xps Measurementsmentioning
confidence: 50%
“…In a Cu-Au ore flotation with chalcopyrite as the major valuable Cu mineral in the presence of bentonite, Wang et al [22] found that divalent cations of Mg 2+ and Ca 2+ had a more significant role than monovalent cations of Na + and K + in reducing bentonite viscosity due to stronger compression of electrical double layers of bentonite particles, thereby increasing flotation efficiency, similar to that found in Hirajima et al [17]. Recently, Li et al [16] reported that at pH 10, the presence of Na + , K + , Ca 2+ increased chalcopyrite recovery due to lower energy barrier for bubble-particle attachments through compressing electrostatic double-layer while the addition of Mg 2+ decreased chalcopyrite flotation efficiency due to the adsorption of formed Mg(OH) 2 precipitation onto chalcopyrite surface to reduce its hydrophobicity. Although these studies focused on the effects of salts on chalcopyrite flotability through investigating the change of particle surface properties, the flotation results varied and even conflicted, keeping underlying mechanisms unclear.…”
Section: Concentrator Location Processing Content Referencesmentioning
confidence: 57%
See 3 more Smart Citations